The Effect of Authentic Leadership on Organizational Citizenship Behavior: The Role of Psychological Empowerment and Quality of Working Life - Alvin Permana Emur; Maulidya Niken Widyasari; Nyimas Ratna Kinnary; Rizky Narendra Putra (Universitas Airlangga, 2023)
Objective: This study aims to investigate the influence of authentic leadership on organizational citizenship behavior (OCB) and examine the role of psychological empowerment and quality of working life (QWL) as mediation in the construction of proposed relationships. Design/Methods/Approach: This study adopts a quantitative method by conducting cross-sectional surveys of multi-sectoral employees in Jakarta, and Surabaya, resulting in 271 respondents. The collected data were analyzed using structural equation models with SmartPLS 3.0 and tested with hierarchical component models or second-order constructs. Findings: The findings of this study show that QWL and psychological empowerment are important variables in mediating the effects of authentic leadership to encourage employees to be willing to demonstrate OCB in the work environment. Originality/Value: This study contributes to the existing literature by investigating the role of psychological empowerment and QWL mediation variables in mediating the indirect influence of authentic leadership on OCB in the Indonesian context. The findings from this study provide theoretical insights and practical implications for authentic leadership in organizations, as well as the foundation for continuous research into QWL and psychological empowerment that may have a solid direct influence and full mediation role on employees' OCB. Practical/Policy implication: Given the results, human resource managers must try their best to fulfill aspects of the quality of working life and increase employee psychological empowerment. Because both variables play an important role in determining the positive effect of authentic leadership on the OCB of employees in the organization